Remembrance and Learning Skills and Their Relationship to Academic Achievement among University Students - Mohammad Omar AL-Momani; Elham Mahmoud Rababa (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The study aimed to identify the memory and learning skills and their relationship to academic achievement among university students in Jordan. The descriptive approach was used in addition to the questionnaire as a tool for the study. The study sample consisted of (1000) university students from different universities, colleges, specializations and levels of study in different Jordanian universities, and the study was applied The study was conducted in the second semester of the academic year (2020-2021), and the study reached a set of results, which is that university students in general possess a high level of learning skills, recall and academic achievement, in addition to the existence of a direct relationship between learning, recall and academic achievement for the members of the research sample . The study found that there are significant differences in the skills of learning, memorization and academic achievement between the academic disciplines of the female students) Scientific and Humanitarian) and for the benefit of scientific specialization .